Better antlers when surrounded by females? The social context influence antler mineralization in pampas deer (Ozotozeros bezoarticus). Issue 4 (4th July 2019) - Ceacero, Francisco; Villagrán, Matías; Gambín-Pozo, Pablo; García, Andrés J.; Cappelli, Jamil; Ungerfeld, Rodolfo
Abstract : Antler growth is a costly yearly process supplied by daily nutrition and body reserves. Conditions for antler growth are rarely optimal. Thus, certain decrease in antler quality due to depletion of resources, known as physiological exhaustion, is frequently observed along the main beam. Testosterone promotes the mineralization in the last phase of antler growth, and its concentration change in male deer according to the socio-sexual environment: it is greater in single males housed only with females than in males housed only with other males (female effect). We hypothesised that the socio-sexual environment affect antler mineralization; especially in the top of the antler which is the last part mineralising and subjected to the described physiological exhaustion, but also the one mineralising when testosterone levels are higher. We tested this in antlers of pampas deer ( Ozotoceros bezoarticus ) from captive animals living in the two social contexts described. All the animals had an ad libitum high nutrition plan, so results are not due to nutritional differences. The antlers from males living with females suffered a lower physiological exhaustion (i.e., lower percent decrease in the top compared to the base of the antler) in the two most important minerals: Ca and P, but also similar tendencies in other bone-biology related trace elements like Sr and Li. Our results highlight that the socio-sexual environment, particularly living continuously in close contact with females, promotes antler mineralization probably through modifications in testosterone secretion.